PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN TANGERANG - Sulaeman, Maman; Metris, Diksi; Rasyiddin, Ahmad (Unperba Press, 2025)
The Community Service Program (PKM) on Sustainable Food Agricultural Land Management was implemented in three sub-districts of Tangerang Regency with a participation rate of 96.67%. This program employed interactive extension methods, including presentations, case studies, simulations, Focus Group Discussions (FGD), and direct land verification and validation activities involving farmers and local government officials. The program successfully increased participants' understanding of Sustainable Food Agricultural Land (LP2B) concepts by 43.6%. Through field verification of 210 locations, it was found that 82.9% still function as productive agricultural land, 10.9% are threatened by land conversion, and 6.2% have been converted to non-agricultural uses. Economic factors (68.7%) were the main drivers of land conversion, followed by farmer regeneration issues (57.3%) and inadequate infrastructure (42.1%). The program formed 9 LP2B guardian groups and encouraged 43 farmers to register their land as LP2B. Policy recommendations include accelerating LP2B designation, developing economic incentive schemes, rehabilitating agricultural infrastructure, and integrating verification data to improve the accuracy of policy-making